Legal Analysis of Criminal Responsibility for Perpetrators of Hate Speech Through Electronic Media Within a Justice-Based Positive Legal Framework - Roynaldo Silaban; Andri Winjaya Laksana (Jurnal Hukum Khaira Ummah, 2025)
This study aims to comprehensively identify and analyze the criminal liability of perpetrators of hate speech through electronic media from a justice-based positive legal perspective. The spread of hate speech through electronic media not only disrupts public order but can also degrade human dignity and deepen social fragmentation. This study was conducted to examine the basis for criminal liability for perpetrators of hate speech from the perspective of Indonesian positive law, while also evaluating the extent to which its implementation reflects the principle of justice for all parties, including perpetrators, victims, and the community. Thus, this study seeks to provide a more proportional understanding of the relationship between freedom of expression and the protection of fundamental social values. This study uses a normative juridical method by adopting a statutory, conceptual, and case study approach. The analysis focuses on provisions in the Electronic Information and Transactions Law (UU ITE), the Criminal Code (KUHP), and several other relevant regulations. This approach is strengthened by a review of legal doctrine and theories of justice to explore the philosophical foundations and objectives of criminal punishment in the context of hate speech. Thus, this study not only examines norms as texts, but also considers ethical values, the principle of proportionality, and aspects of human rights protection, which are integral parts of the legal system. The results explain and demonstrate that the basis for criminal liability for perpetrators of hate speech via electronic media is formally regulated within Indonesia's positive legal framework. However, its implementation has not been fully effective in delivering substantive justice. This is due to several obstacles, including unclear norms, overlapping regulations, and the potential for misuse of articles by law enforcement officials. Furthermore, the application of the law often fails to consider the social context, the perpetrator's motives, and the real impact on the victim. Therefore, regulatory harmonization, more proportional application of the law, and an approach that favors substantive justice are needed so that the handling of hate speech can truly protect the public interest without neglecting the constitutional right to freedom of expression.